Metaproteogenomic analysis of microbial communities in the phyllosphere and rhizosphere of rice - Knief, Claudia; Delmotte, Nathanaël; Chaffron, Samuel; Stark, Manuel; Innerebner, Gerd; Wassmann, Reiner; von Mering, Christian; Vorholt, Julia A. (Oxford University Press, 2012)
The above- and below-ground parts of rice plants create specific habitats for various microorganisms. In this study, we characterized the phyllosphere and rhizosphere microbiota of rice cultivars using a metaproteogenomic approach to get insight into the physiology of the bacteria and archaea that live in association with rice. The metaproteomic datasets gave rise to a total of about 4600 identified proteins and indicated the presence of one-carbon conversion processes in the rhizosphere as well as in the phyllosphere. Proteins involved in methanogenesis and methanotrophy were found in the rhizosphere, whereas methanol-based methylotrophy linked to the genus Methylobacterium dominated within the protein repertoire of the phyllosphere microbiota. Further, physiological traits of differential importance in phyllosphere versus rhizosphere bacteria included transport processes and stress responses, which were more conspicuous in the phyllosphere samples. In contrast, dinitrogenase reductase was exclusively identified in the rhizosphere, despite the presence of nifH genes also in diverse phyllosphere bacteria.